Development of the Adrenal Gland in the Crossbred Goat - Ashok N (Department of Anatomy, College of Veterinary and Animal Sciences, 1999)
Studies on the prenatal and postnatal development of the adrenal gland in crossbred goats were conducted using 55 embryos/ foetuses of varying gestational ages and 45 goats from day old to 180 days postpartum. The project was taken up to trace the normal growth and developmental pattern of the glands and their relationship with age, body weight and the physiological status. After recording gross relations and measurements, the material was fixed using various fixatives for studying the cellular details, arrangement of cells, connective tissue framework, micrometry and histochemistry. The glands attained their characteristic shapes even during early development and were located cranial to the kidneys in the retroperitoneum. During the prenatal period weight of the adrenals increased steadily upto 141 days followed by a spurt thereafter due to the hypertrophy and hyperplasia of the cortex. After birth also an increasing trend was noticed in adrenal weight from birth to 180 days with a slight decrease at 45 days. The glandular weight was positively correlated with age and body weight. The proportion of the adrenal to body weight percentage showed a decreasing trend in both the groups studied. The left gland was slightly heavier and longer than the right while the right one was broader and thicker. The length, breadth and